URGENSI REKONSTRUKSI MAHKAMAH KONSTITUSI DALAM MEMBERIKAN PERTIMBANGAN KEBIJAKAN HUKUM TERBUKA (OPEN LEGAL POLICY) - Fauzani, Muhammad Addi; Rohman, Fandi Nur (Justitia et Pax, 2019)
This research has two problem formulations, First, how the Constitutional Court's construction in giving consideration to "open legal policy"; Second, what is the urgency of the Constitutional Court's reconstruction in giving consideration to"open legal policy"? This research uses a normative juridical study using the statutory and conceptual approach. The results of this study are: First, that is a lack of clarity and consistency from the Constitutional Court in determining benchmarks for open legal policy considerations. Second, there are new concept been proposed: a) applying the doctrine of "political question"; b) The Constitutional Court still tests a norm based on formal and substantial requirements. The advice given is that Constitutional Court should take a position in accordance with the reconstruction proposed in this study.